2017
DOI: 10.1007/s00192-017-3379-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to justify retention of transvaginal mesh: comparison between laparoscopic sacral colpopexy and transvaginal Elevate™ mesh

Abstract: Transvaginal Elevate™ mesh delivers comparable apical support with a low exposure rate similar to that of laparoscopic sacral colpopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…There were 20 eligible studies, including four RCTs [18][19][20][21][22] (there were two articles 20,21 about one RCT), four prospective studies [23][24][25][26] and 12 restrospective studies, [27][28][29][30][31][32][33][34][35][36][37][38] identified from the MEDLINE, EMBASE, Cochrane Library and clinicaltrials.gov databases. A PRISMA flow diagram depicting the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 20 eligible studies, including four RCTs [18][19][20][21][22] (there were two articles 20,21 about one RCT), four prospective studies [23][24][25][26] and 12 restrospective studies, [27][28][29][30][31][32][33][34][35][36][37][38] identified from the MEDLINE, EMBASE, Cochrane Library and clinicaltrials.gov databases. A PRISMA flow diagram depicting the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Four RCTs [18][19][20][21][22] and six NRSIs 23,24,26,28,32,38 were included. A meta-analysis of the reoperation rate showed very-lowquality evidence suggesting no difference between the Figure 3B).…”
Section: Reoperation For Pop Recurrencementioning
confidence: 99%
See 3 more Smart Citations